Organizational justice: unveiling best practice in the hospitality realm / Nurfatihah Mazlan, Norzuwana Sumarjan and Wan Hayati Wan Bujang - Mazlan, Nurfatihah; Sumarjan, Norzuwana; Wan Bujang, Wan Hayati (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
Hotel organizations strive to foster and maintain high-quality relationships with its internal and external stakeholders. Internally, organizational justice is one of the vital components in human resources management to encourage employee’s commitment. It is how employees perceive fairness in an organization through four subdimensions which are distributive, procedural, informational and interrelation. This study aims to explore the best practice of organizational justice in Malaysia hotel industry. Seven interviews were conducted with managers and directors of human resource from four- and five-stars hotels in central region of Malaysia. The majority on the hotels emphasized on procedural justice with plenty of fair practices and policies pertaining to employee’s evaluation, training, reward system and leadership. Findings also reveal several practices related to interpersonal, informational, and distributive justice. This study provides guidance to managers on some of the best practice to instill justice within the organization.